Multiple Identified Neurons and Peripheral Nerves Innervating the Prothoracic Defense Glands in Stick Insects Reveal Evolutionary Conserved and Novel Elements of a Chemical Defense System - Strauß, Johannes; von Bredow, Christoph-Rüdiger; von Bredow, Yvette M.; Stolz, Konrad; Trenczek, Tina E.; Lakes-Harlan, Reinhard (Frontiers in Ecology and Evolution, 2017)
The defense glands in the dorsal prothorax are an important autapomorphic trait of stick insects (Phasmatodea). Here, we study the functional anatomy and neuronal innervation of the defense glands in Anisomorpha paromalus (Westwood, 1859) (Pseudophasmatinae), a species which sprays its defense secretions when disturbed or attacked. We use a neuroanatomical approach to identify the nerves innervating the gland muscles and the motoneurons with axons in the different nerves. The defense gland is innervated by nerves originating from two segments, the suboesophageal ganglion and the prothoracic ganglion. Axonal tracing confirms the gland innervation via the anterior suboesophageal nerve, and two intersegmental nerves, the posterior suboesophageal nerve and the anterior prothoracic nerve. Axonal tracing of individual nerves reveals eight identified neuron types in the suboesophageal or prothoracic ganglion. The strongest innervating nerve of the gland is the anterior suboesophageal nerve, which also supplies dorsal longitudinal thorax muscles (neck muscles) by separate nerve branches. Tracing of individual nerve branches reveals different sets of motoneurons innervating the defense gland (one ipsilateral and one contralateral suboesophageal neuron) or the neck muscle (ventral median neurons). The ipsilateral and contralateral suboesophageal neurons have no homologs in related taxa like locusts and crickets, and thus evolved within stick insects with the differentiation of the defense glands. The overall innervation pattern suggests that the longitudinal gland muscles derived from dorsal longitudinal neck muscles. In sum, the innervating nerves for dorsal longitudinal muscles are conserved in stick insects, while the neuronal control system was specialized with conserved motoneurons for the persisting neck muscles, and evolutionarily novel suboesophageal and prothoracic motoneurons innervating the defense gland.